From Krasner’s Corpoid and Bourbaki’s Graduations to Krasner’s Graduations and Krasner-Vuković’s Paragraduations - Vuković, Mirjana (Sarajevo Journal of Mathematics, 2019)
The paper, supplemented with a short historical development of graduation which begins with Krasner’s famous notion of a corpoid, introduced in 1940s and general graded groups in Krasner’s sense, more general than Bourbaki’s, will present some results in the theory of Krasner-Vukovi´c’s para- and extra-graded groups including examples of paragraduations which are and which are not graduations, and some proofs of statements that were not given earlier.